Characteristics of the anaerobic metabolism capacity of elite Chinese style wrestlers - Zhang, M. L. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: An assessment of maximal sustainable performance capacity of 10s, 30s, and 60s Wingate tests, enabled the present study to determine characteristics of the energy supply capacity of phosphate and glycolysis and anaerobic metabolism. Elite Chinese-style wrestlers of different genders and training levels participated in the study to provide a reference for scientifically-based training. Methods The subject group consisted of 27 elite Chinese-style wrestlers, including 10 national-class master athletes, 7 first-class athletes, 10 second-class and other class athletes participated in the study. 1. The maximal sustainable performance capacity was measured using a powermax-VII ergometer. 2. Blood lactic acid concentrations were measured using a YSI-1500 Blood lactate analyzer. 3. HR was measured by stopwatch. 4. The data were processed using SPSS 11.0.3. The indices included maximal power (MP), relatively maximal power (MP/Kg), maximal flywheel count (Cmax), time of maximal flywheel count (Cmax-time), average power (AP), relatively average power (AP/Kg), rate of power drop (P-drop), heart rate at rest (HR), instant heart rate (i-HR), 3-minute recovery heart rate after exercise (HR-3), and blood lactic acid after exercise (Bla). Results 1. The results showed significant differences in anaerobic metabolism capacity between the male players and the female players. The males` capacities of MP (P<0.01), MP/Kg (P<0.05), and Cmax (P<0.05) of the 10s, 30s, and 60s tests were much higher than the females`. 2. The MP and AP of the elite male group were higher than those of the ordinary group during 10s, 30s, and 60s tests (P<0.05), but the MP/Kg and AP/Kg were similar. 3. The MP and AP of the elite female group were higher than those of the control group during the 10s, 30s, and 60s tests (P<0.05), but only the10s power test had statistical significant differences. 4. The peak blood lactic of the elite male and female group was lower than that of the ordinary group in the 10s test, but this effect was opposite during the 30s and 60s tests; differences were not statistically significant.. Conclusions 1.The elite Chinese-style wrestlers had better capacities of energy supply of phosphate and glycolysis, and the male wrestlers` capacities of energy supply of phosphate and glycolysis were higher than the female wrestlers. 2. Compared with the elite cyclists, weightlifters, and gymnastics, the elite Chinesestyle wrestlers` MP, speed, endurance, and glycolytic capacity were lower. Compared with Wush sanda players, the elite female Chinese-style wrestlers` maximal power, speed, endurance, and glycolytic capacities were higher. 3. There were significant differences in the capacity of energy supply of phosphate and glycolysis between male and female Chinese-style wrestlers of different levels, and the capacities in the elite male and female groups were better than the ordinary male and female groups. 4. It is suitable and objective to put the index of blood lactic acid and the 10s, 30s, and 60s anaerobic tests together for evaluating the anaerobic metabolism capacity of elite Chinese-style wrestling male and female players.